2023
DOI: 10.1038/s41598-023-33134-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks determination of material elastic constants and structures in nematic complex fluids

Abstract: Supervised machine learning and artificial neural network approaches can allow for the determination of selected material parameters or structures from a measurable signal without knowing the exact mathematical relationship between them. Here, we demonstrate that material nematic elastic constants and the initial structural material configuration can be found using sequential neural networks applied to the transmmited time-dependent light intensity through the nematic liquid crystal (NLC) sample under crossed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the study, 89 authors have demonstrated that material nematic elastic constants and the initial structural material configuration can be determined using sequential neural networks applied to transmitted time-dependent light intensity through a nematic liquid crystal sample under crossed polarizers. Multiple simulations were conducted for the nematic's relaxation from a random initial state to equilibrium, considering random elastic constants.…”
Section: Main Textmentioning
confidence: 99%
“…In the study, 89 authors have demonstrated that material nematic elastic constants and the initial structural material configuration can be determined using sequential neural networks applied to transmitted time-dependent light intensity through a nematic liquid crystal sample under crossed polarizers. Multiple simulations were conducted for the nematic's relaxation from a random initial state to equilibrium, considering random elastic constants.…”
Section: Main Textmentioning
confidence: 99%
“…36 Another example is the prediction of elastic constants in relation to experimental and simulated curves. 37 Also melting temperatures have been shown to be predictable, 38 as has structural colour, i.e. selective reflection in formulation space, 39 or minimisation of threshold voltages in ZnO doped liquid crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been used to characterize liquid crystal properties based on the material structure. For example, elastic constants have been determined from polarized light microscopy images of nematic liquid crystals [29]. Transmittance and luminance have also been predicted based on polarized optical microscopy images.…”
Section: Introductionmentioning
confidence: 99%